Retropupillary fixated iris-claw lens: An effective alternative for aphakia - Kishore Kumar Proddatoori; Sai Divya Jajapuram; Sasi Pyda; Shahin Zamrudh (Journal of Clinical Ophthalmology and Research, 2018)
Context: Visual rehabilitation in aphakia has been a challenge with a wide variety of surgical options available for the ophthalmologist. We report the visual outcome with retropupillary fixated iris-claw lens secondary to intraoperative complications and secondary implantation in aphakia. Aims: This study aims to evaluate the postoperative visual acuity and complications of retropupillary fixated iris-claw intraocular lens (IOL) implantation in the management of aphakia. Settings and Design: This was a prospective interventional case series. Subjects and Methods: An interventional study on 50 eyes of 50 patients fulfilling the inclusion criteria was conducted. Preoperative visual acuity, slit-lamp examination, and fundus examination were carried out. Anterior vitrectomy and retropupillary fixation of iris-claw lens were done. The primary outcome measure was postoperative best-corrected visual acuity (BCVA) and the secondary postoperative complications were recorded at various intervals following surgery for 6 months. Results: The final BCVA in 80% of the patients at 6 months ranged from 6/12 to 6/6. The common complications noted were pupillary distortion (34%), pigment clumping over the IOL (20%), iris chaffing at the enclaved site (28%), and secondary glaucoma (12%). Retinal detachment was noted in one patient secondary to trauma after the surgery. No patient had complications such as corneal decompensation, IOL dislocation, cystoid macular edema, and endophthalmitis. Conclusions: Our study suggests that retropupillary fixated iris-claw IOL is an effective, safe, and simple procedure with minimal surgical time for visual rehabilitation in aphakia with less incidence of visually threatening complications. Its posterior location decreases the incidence of corneal decompensation. It is an effective procedure for primary implantation with intraoperative posterior capsular rent and severe zonular dialysis.